치과용엑스선장치의 기술문서 작성을 위한 가이드라인 개발 연구 - 이승열(Seung-Youl Lee); 김재량(Jae-Ryang Kim); 이준호(Jun-Ho Lee); 박창원(Chang-Won Park) (방사선기술과학, 2016)
Due to recent population aging, the number of check-up for senior citizens has increased steadily. According to this trend, the market size of dental X-ray equipment and the number of approval and review for these devices have simultaneously increased. The technical document of medical device is required for approval and review for medical device, and medical device companies needs to have work comprehension and expertise, as the document needs to include the overall contents such as performances, test criteria, etc.. Yet, since most of domestic manufacturers or importers of medical devices are small businesses, it is difficult for them to recruit professional manpower for approval of medical devices, and submission of inaccurate technical documents has increased. These problems lead to delay of the approval process and to difficulties in quick entering into the market. Especially, the Ministry of Food and Drug safety (MFDS) standards of a dental extra-oral X-ray equipment, a dental intra-oral X-ray equipment, an arm-type computed tomography, and a portable X-ray system have been recently enacted or not. this guideline of dental X-ray equipment adjusting revised standards was developed to help relative companies and reviewers. For this study, first, the methods to write technical document have been reviewed with revised international and domestic regulations and system. Second, the domestic and foreign market status of each item has been surveyed and analyzed. Third, the contents of technical documents already approved by MFDS have been analyzed to select the correct example, test items, criteria, and methods. Finally, the guideline has been developed based on international and domestic regulation, through close review of a consultative body composed of academic, industrial, research institute and government experts. 최근 인구고령화로 인하여 치과진료 주요대상인 노인층의 검사가 꾸준히 증가하고 있다. 따라서 치과 진단용 엑스선장치 시장도 꾸준히 성장하고 있으며, 동시에 치과용엑스선장치의 허가 심사건수도 증가하고 있다. 의료기기 기술문서는 의료기기의 허가 심사 시 필수로 요구되는 자료이며, 해당 의료기기의 전반적인 항목을 기술해야 하는 만큼 작성자의 업무 이해도 및 전문성이 필요하다. 그러나 국내 의료기기 제조 수입 업체 대부분이 영세하여 의료기기 인 허가 관련 전문 인력의 확보가 쉽지 않아, 이로 인한 기술문서의 부정확한 작성이 증가하고 있다. 이에 따른 심사자의 민원 처리 지연과, 제품의 신속한 시장 진입의 어려움이 발생되고 있다. 특히 치과용구강외엑스선장치, 치과용구강내엑스선장치, 암형전산화단층엑스선촬영장치, 포터블엑스선 촬영장치(이하 치과용엑스선장치)는 식품의약품안전처 기준 규격이 최근에 제정되거나 부재한 품목으로, 의료기기 제조 수입업체에서 시험항목 설정 시 많은 어려움을 겪고 있기에, 개선된 규격이 반영된 치과용엑스선 장치 가이드라인(안)을 개발하여 관련 업체 및 심사자에게 도움을 주고자 한다. 본 연구를 위하여 첫째, 기술문서에 대한 개선된 제도 운영 조사 및 의료기기의 제도 적용에 따른 문서 작성 방법을 검토하였으며, 둘째, 품목별 시장현황을 조사하고, 국내 외 규격을 분석하였으며, 셋째, 기 허가된 제품의 기술문서를 분석하여 품목별 올바른 작성방법과 국제조화된 시험항목, 기준 및 방법을 도출하였다. 마지막으로, 산 연 관 전문가 협의체 회의를 통하여, 공정하고 전문성이 강화된 기술문서 작성 가이드라인(안)을 도출하였다.